Genetic variability in Mazama genus based on transferrin, seric albumin, and hemoglobin polymorphism - Garcia, José Eduardo; Ramos, Paulo Roberto R.; Bortolozzi, Jehud; Duarte, José Maurício B. (SITIENTIBUS série Ciências Biológicas, 2007)
The genus Mazama is currently represented in Brazil by five species: M. nana, M. americana, M. gouazoubira, M. bororo, and M. nemorivaga. The objective of the present study was to determine the electrophoretic characteristics of transferrin, serum albumin, and hemoglobin in the genus Mazama in order to evaluate the polymorphism among different species in Brazil. Blood samples from 138 animals, kept in captivity and with a known origin in nature and coming from all regions of the country, were studied by polyacrylamide gel electrophoresis. Variability for the transferrin locus ranged from monomorphism in M. nana and M. bororo to six different electromorphs in M. gouazoubira. Monomorphism was found at the serum albumin locus but two alleles were observed in M. gouazoubira. Hemoglobin presented three phenotypes but no significant differences in gene frequencies were observed.